Trandix: proactive tool to terminological searches by translators and its assessment - Durán Muñoz, Isabel; Fernández Sola, Alejandro (MonTi Monografías de Traducción e Interpretación, 2015)
This paper analyses current trends in the terminography field and translators’ needs regarding terminology resources. In this context, the Trandix tool is presented as a novel software application that pursues efficiency in terminological searches conducted by translators. This tool is based on Tarp’s Function Theory of Lexicography (2008a) and Spohr’s proposal concerning electronic multifunctional dictionaries (2009). A further goal of this paper is to serve as an example for future research in terminological resources aiming to meet translators’ requirements and expectations when carrying out terminology searches